Authentication of commercially important tuna species landed in Tuticorin coast of Tamil Nadu, India by SE-AFLP method - Jeyasekaran, G.; Arunkumar, G.; Kumar, P. Senthil; Shakila, R. Jeya; Sukumar, D. (Indian Journal of Fisheries, 2018)
Seafood serves as a valuable protein source for human population. Among the seafood, tuna is considered as one of the commercially important species worldwide. Five tuna species namely Euthynnus affinis, Auxis thazard, Katsuwonus pelamis, Thunnus albacares and Thunnus obesus are commonly landed in the Tuticorin coast of Tamil Nadu. Among the five species, the exportable quality and grade of the meat is as follows: T. albacares> T. obesus> K. pelamis> E. affinis> A. thazard. In recent years, mislabeling is done by replacing high value tuna meat with low value tuna meat or with other low value fish meat to earn illegally. Usually, the species identification is done based on the morphological features, but this cannot be applied for the processed fish. PCR based identification methods have gained importance in the identification of fish species. PCR-AFLP is one of the molecular based methods, which can differentiate even closely related species. In this study, SE-AFLP method was employed to differentiate the above five tuna species viz., E. affinis, A. thazard, K. pelamis, T. albacares and T. obesus. Species specific AFLP marker was obtained in the primer combination of EcoR1 for fresh tuna. Band Sharing Index (BSI) analysis was also performed to find the similarities and variation among the five tuna species. AFLP profile of unknown tuna products was compared with the standard AFLP profile and the tuna species authentication was done by analysing BSI score.